2006
DOI: 10.1093/bja/ael253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intubation dose of rocuronium on Spectral Entropy and Bispectral Index™ responses to laryngoscopy during propofol anaesthesia

Abstract: Rocuronium alters the RE-SE gradient and the RE and RE-SE responses to laryngoscopy. Muscle relaxation may confound interpretation of entropy monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…The major concern is that EMG signal can be abolished with neuromuscular blocking agents and the loss of his high-frequency signal may be interpreted as an increase in anaesthesia depth; neuromuscular blockers giving a false impression of deepening anaesthesia. There is now ample evidence that this is a real phenomenon [81][82][83][84][85]. There is no reason to think this issue would not be relevant to paediatric anaesthesia.…”
Section: Effect Of Neuromuscular Blockadementioning
confidence: 99%
“…The major concern is that EMG signal can be abolished with neuromuscular blocking agents and the loss of his high-frequency signal may be interpreted as an increase in anaesthesia depth; neuromuscular blockers giving a false impression of deepening anaesthesia. There is now ample evidence that this is a real phenomenon [81][82][83][84][85]. There is no reason to think this issue would not be relevant to paediatric anaesthesia.…”
Section: Effect Of Neuromuscular Blockadementioning
confidence: 99%
“…It has been shown that these commercially available parameters do not change in parallel with each other during anaesthesia or sedation. [3][4][5][6][7][8][9] Some studies have reported 'paradoxical' changes and inaccurate readings of index values. While complex statistical analyses have been applied in these studies, no attempt has been made to try to explain the electrophysiological background for disagreement between the numerical values of BIS and Entropy.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…The level of muscular block and EMG activity should also be taken into account during monitoring. Many studies have shown that the level of muscular block can interfere with the values of EEG-based monitoring [64,65]. BIS monitoring may not perform reliably with all anesthetics.…”
Section: Limitations Of Eeg-based Monitoring Of Hypnosismentioning
confidence: 99%